DETERMINATION OF SIFIs (SYSTEMATICALLY IMPORTANT FINANCIAL INSTITUTIONS) AMONG INDONESIAN BANKS USING NETWORK ANALYSIS APPROACH - Anggayasti Hayu Anindita; Zaafri Ananto Husodo (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2017)
This study aims to measuring systemic risks using network analysis method to obtain the SIFI rating of Indonesian banks. We analyze the systemic risk implied in the Indonesian interbank network during the period from 2011 through 2015 based on various network measures such degree centrality and betweenness centrality. The main findings are as follows: First, interconnectedness in the interbank market increased. However, a significantly different condition was found in 2013, in which the interconnectedness in the interbank market went downwards compared to the previous year. Second, the degree centrality score showed that government-owned and national private banks tend to be in-degree while foreign private banks tend to be out-degree. Third, there was no bank that consistently continued to have a high betweeness centrality score during the study period.